Characteristics of pregnancy, delivery and newborn children in the City of Huaraz, 2001-2005 - Gonzales, Gustavo F. (2024)
This is a descriptive study on the maternal population in Huaraz City at 3052 m in the central highlands of the Departament of Ancash.  Objetive: to record sociodemographic characteristics of pregnant women, and conditions associated with pregnancy, delivery and newborn children.  Materials and methods: cross-sectional and descriptive study based on history records from the pregnancies attended from 2001 to 2005 at the Hospital Víctor Ramos Guardia, City of Huaraz. The sample included 10 354 deliveries, at from 28 to 42 weeks of pregnancy.  Results: The mean hemoglobin value was 12,84 g/dL (± 1,36). According to Ministry of Health (MINSA) guidelines which correct hemoglobin values according to altitude of residence, the prevalence of anemia was 49,67 %. Out of all mothers, 42 % were primiparas, 48% had had several pregnancies, and a low percentage of women had great multiparity. Seventy-seven percent of the women had more than 4 prenatal care visits. Seventeen percent had at least one abortion; 6,5% had a previous cesarean section. Among complications during pregnancy, preeclampsia was observed in 5.25% of cases, urinary infections in 31,41% and twin births in 1.96% of cases. Mean birthweight was 3 051,74 g (± 550). The mean gestational age according to the last menstrual period was 38,2 ± 2,0 weeks. Incidence of pre-term deliveries was 9% and small for gestational age newborns were 16,6 %.  Conclusions: characteristics of pregnancy, delivery and neborn children in Huaraz are similar to those of the central Andes and different to those observed in the southern Andes.